(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The present article addresses the developments of using online conflict resolution in Brazil and the possibility of it being an instrument of citizenship in the digital age, capable of redefining the concept of access to justice through the vast Brazilian legislative, doctrinal, and jurisprudential apparatus. Additionally, it discusses Theme 91 ruled by the Court of Justice of the State of Minas Gerais, a judicial precedent that encourages the use of online conflict resolution methods, either before or alternatively to the procedural phase, as a condition of the action or the interest to act, which are procedural assumptions. Through the deductive method, the research establishes a dialogue with the subjects of Constitutional Law, Collective Law, and Civil Procedural Law, which allowed for a conclusive response to the raised question, demonstrating that Brazilian jurisprudence has supported the use of online means for conflict resolution as a possible alternative to mass judicialization before the Judiciary. Through this article, it is promoted, without exhausting the subject, that access to jurisdiction can play a subsidiary role in society, especially given the narrowing of borders, speed, efficiency, and cost reduction offered by online conflict resolution methods to those interested in facing a resisted claim, which can be resolved extrajudicially.